Optimal portfolio selection in an Itô-Markov additive market - Zbigniew Palmowski; Łukasz Stettner; Anna Sulima (Risks, 2019)
We study a portfolio selection problem in a continuous-time Itô-Markov additive market with prices of financial assets described by Markov additive processes that combine Lévy processes and regime switching models. Thus, the model takes into account two sources of risk: the jump diffusion risk and the regime switching risk. For this reason, the market is incomplete. We complete the market by enlarging it with the use of a set of Markovian jump securities, Markovian power-jump securities and impulse regime switching securities. Moreover, we give conditions under which the market is asymptotic-arbitrage-free. We solve the portfolio selection problem in the Itô-Markov additive market for the power utility and the logarithmic utility.
Keywords: 330; Markov additive processes; Markov regime switching market; Markovian jump securities; asymptotic arbitrage; complete market; optimal portfolio